1993
DOI: 10.1007/bf00942783
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV in human vitreous

Abstract: Assay of human vitreous specimens obtained postmortem for HIV antibodies, or HIV p24 antigen, is reported to be a reliable technique to demonstrate HIV infection in possible cornea donors from whom serum could not be obtained. We tested three vitreous samples obtained during vitrectomy from two HIV-positive patients. One patient exhibited the clinical AIDS syndrome. HIV antigen and antibody tests were negative in all specimens. HIV proviral DNA was detected by PCR only in the vitreous of the patient with AIDS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Some post‐mortem studies used different tissues to ascertain if a certain tissue might be more effective compared to blood or serum. These tissues included pleural fluid (Douceron et al , ), pericardial fluid (Douceron et al ), skin (Gala et al ), lymph nodes (Nyberg et al ; Ball et al ; Padley et al ), bile (Karhunen et al ), lung (Ball et al ), brain (Nyberg et al ; Ball et al ), spleen (Nyberg et al ; Ball et al ), cerebrospinal fluid (Nyberg et al ; Ball et al ), bone (Nyberg et al ; Salzman et al ), bone marrow (Nyberg et al ) and vitreous fluid (Pepose et al ; Klatt et al ; Mietz et al ; Karhunen et al ; Schor et al ). In the majority of cases, HIV could be detected in most samples, with similar reliability to blood or serum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some post‐mortem studies used different tissues to ascertain if a certain tissue might be more effective compared to blood or serum. These tissues included pleural fluid (Douceron et al , ), pericardial fluid (Douceron et al ), skin (Gala et al ), lymph nodes (Nyberg et al ; Ball et al ; Padley et al ), bile (Karhunen et al ), lung (Ball et al ), brain (Nyberg et al ; Ball et al ), spleen (Nyberg et al ; Ball et al ), cerebrospinal fluid (Nyberg et al ; Ball et al ), bone (Nyberg et al ; Salzman et al ), bone marrow (Nyberg et al ) and vitreous fluid (Pepose et al ; Klatt et al ; Mietz et al ; Karhunen et al ; Schor et al ). In the majority of cases, HIV could be detected in most samples, with similar reliability to blood or serum.…”
Section: Resultsmentioning
confidence: 99%
“…As vitreous humor can easily be retrieved from the body, several researchers tested vitreous humor for HIV. Unfortunately, most studies concluded that testing vitreous humor was unreliable compared to other bodily fluids because a high false negative rate was reported (Pepose et al ; Klatt et al ; Mietz et al ; Schor et al ). In contrast, Karhunen et al () consistently detected HIV in vitreous fluid using several different types of tests.…”
Section: Resultsmentioning
confidence: 99%
“…Even removal of the vitreous carries a small risk of needle stick injuries, and the vitreous is known to harbour pathogens such as human immunodeficiency virus. 22 In addition to the usual infectious agents potentially encountered at necropsy, 3 the eye is one of the tissues with the highest titres of infectivity for the human and animal transmissible spongiform encephalopathies, and infectivity is present in unfixed or routinely fixed tissues. 23 In view of the small risk of infection of necropsy workers, the advisory committee on dangerous pathogens and Department of Health have issued guidelines for the UK, which are considered to represent "good practice".…”
Section: Health and Safety Considerationsmentioning
confidence: 99%